An easy and practical prognostic parameter: tumor–stroma ratio in Luminal, Her2, and triple-negative breast cancers - Öztürk,Çiğdem (2022)
SUMMARY OBJECTIVE: The stroma surrounding the tumor cells is important in tumor progression and treatment resistance, besides the properties of tumor cells. Studies on the tumor stroma characteristics will contribute to the knowledge for new treatment approaches. METHODS: A total of 363 breast cancer patients were evaluated for the tumor–stroma ratio. The percentage of stroma was visually assessed on hematoxylin–eosin stained slides. The cases of tumor–stroma ratio more than 50% were categorized as tumor–stroma ratio high, and those less than 50% and below were categorized as tumor–stroma ratio low. RESULTS: Tumor–stroma ratio-high tumors had shorter overall survival (p=0.002). Disease-free survival tended to be shorter in tumor–stroma ratio-high tumors (p=0.082) compared with tumor–stroma ratio-low tumors. Tumor–stroma ratio was an independent prognostic parameter for the total group of patients (p=0.003) and also axillary lymph node metastasis and tumor–stroma ratio was statistically associated (p=0.004). Also, tumor–stroma ratio was an independent prognostic parameter in node-positive Luminal A and B subgroups for overall survival (p<0.001). CONCLUSION: Tumor–stroma ratio is an independent prognostic parameter that can be evaluated quite easily in all molecular subtypes of all breast cancers and does not require extra cost and time to evaluate.